(3OjhGf GdHMQGfjs - (3GdHMQGfj, GdMSjfj, CHh Ydj, eGLO Hf gGTe Hf Ydj Hf GdeQJVi, J (B1022(3g`s ((3eMeO GdSeGhjs)
(3ChdgG (B:s
(3Hci hdjS Ydi UHQ HeYPhQ(B***(3ef bO CWd Ydjg YTQ YGThQs
(3BNQgG (B:s
(3aCUHMJ eJQha GdaDGO cCfeG(B***(3SbJfj YbGQG BNQ Gddjd UQNOs
(3JHUQI GdeDda (B:s
(3SfI haGJg aj gOjI GdYGQajf(B: 1028(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B5s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B1s
(3GdPQjYI, Qbe(B: 6235s
Keywords: (3GdCOHs